Electricity Generation Cost Under a reform of the Electric Supply Industry in Thailand - Supattana Nirukkanaporn; Kumar, Sivanappan; Honda, Kiyoshi; Salam, Abdul P.; Sharma, Deepak (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
To achieve higher efficiency and yield highest net profit to the electricity generation {u2013} supply system, developed and developing count ries around the world have embarked on electric supply industry (ESI) reform. The first ESI reforms allowed investment in electricity generation by the private sector. The vertically -integrated monopoly (VIM) ESI structure was transformed to the single-buyer (SB) structure through an independent power producer (IPP) scheme. This approach resulted in a reduction in the financial obligations required by the government sector and induced pr ivate investment in capacity expansion to satisfy the growing electricity demand. For exam ple, in 2010, the installed capacity of IPPs in the total supply system of Th ailand will be more than 45%. ESI reform intoto a competitive market has be en implemented in developed countries with many suggestions. However, ESI is complex and each environment/country has its own characteristics, resources, policies, and sp ecific constraints for its implementation and operation. International reform experiences unde rline the need for a careful study on these after effects prior to implementing any reform st ructure. Therefore, careful analysis across different dimensions needs to be performed. The traditional power purchase agreements (PPAs) have given no incentives for the independent power producer to improve their efficiency. The availability payment mostly covers the cost of IPP and there is no market risk for such IPP. Inefficient operation of the SB with IPP scheme has been widely mentione d in the literatures due to such PPA{u2019}s. The availability payment is designed to cover capita l cost of IPP while energy payment ensures that IPP will be financially viable. Ineffi cient clause of PPA can induce efficient investment but not sufficient to achieve the operating benefits of competition. Thailand plans to continue the SB (now modified to enhanced single buyer {u2013}ESB) with such an IPP scheme. This research, therefore, aims to conduct quantitative analyses on such inefficiencies, specifically the el ectricity generation cost as the major focus, as this directly reflects the electricity tariff. The terms of PPA which includes the virtual must-run clause and other clause specified to let IPP operates as baseload generation, such as limited daily load range constraint are the operational constraints incorpor ated in the analysis, which will affect the energy payment component of power generation. The objectives of the study are, therefore, to first analyze the problem or constraints on the operation of the present ESI stru cture of the reference system (SB), and secondly to study if a reform ESI structure (transitional-TR m odel) using a competitive PPA works. That is, whether or not it leads to better opera ting conditions and redu ces system operating constraints. In other words, will it yield lower electricity cost while still maintaining reliability criteria. The Thailand electr icity sector is taken as the case study. The research process consists of two steps: - Formulation of the reference power syst em to perform operational analysis: The reference power system was derived by the expansion of the Thai power system by applying demand growth forecasted, and by using WASP-IV for least-cost generation expansion plan. The expanded power system of year 2010 was taken to be the reference system for the operation analysis. - Operational analysis of the reference power system for different ESI structures. The simulations were conducted based on unit commitment UC scheduling of generation with pre-hydro peak shaving or peak shav ing method (PSM). The observed parameters.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Electric Power System Managemen, School of Environment, Resources and Development
Keywords: Electricity -- Costs; Electric utilities -- Thailand